THE EFFECT OF CODED AND NON-CODED CORRECTION FEEDBACK ON THE QUALITY OF INDONESIAN EFL STUDENTS’ WRITING - Saukah, Ali; Dewanti, Desak Made Indah; Laksmi, Ekaning Dewanti (Indonesian Journal of Applied Linguistics, 2017)
Written corrective feedback (WCF) in L2 writing classrooms has gained considerable attention in applied linguistics research over the past twenty years. WCF may take different forms of teacher’s responses to errors in students’ texts, among others Coded-Correction Feedback (CCF) and Non-Coded Correction Feedback (NCCF). A number of research studies on the effectiveness of various types of corrective feedback have been undertaken; however the effect of CCF and NCCF on the quality of students’ writing in Indonesian context has not yet been explored. The objective of this study was to investigate the effects of Coded Correction Feedback and Non-Coded Correction Feedback on senior high school students’ writing quality. This study investigated the effect of Coded-Correction Feedback (CCF) and Non-Coded Correction Feedback (NCCF) on the quality of Indonesian EFL students’ writing. It involved 53 senior high school students of 11th Grade. Each student was exposed to two different treatments (CCF and NCCF) and the students’ writing quality, after receiving each type of treatments or WCF, was then measured. The effect of each feedback was estimated by comparing the individual students’ scores in writing composition after receiving CCF with their scores after receiving NCCF. The result of this study revealed that the quality of the students’ writing with CCF was better than that with NCCF. The findings of this study showed that the quality of the students’ writing receiving CCF was better than that receiving NCCF because CCF promotes awareness with noticing as well as understanding. Hence, the use of CCF can be considered more effective than NCCF.  Therefore, it is suggested that CCF be employed in giving corrective feedback to the students’ compositions to improve the quality of their writing, and that teachers employ CCF when giving WCF to improve the quality of students’ writing.